Environmental noise and sleep disturbance: research in Central, Eastern and South-Eastern Europe and Newly Independent States - Ristovska, Gordana; Lekaviciute, Jurgita (Medknow, 2013)
Countries from South-East Europe (SEE), Central and Eastern Europe (CEE) and Newly Independent States (NIS) are in the process of harmonization with European environmental noise legislation. However, research work on noise and health was performed in some countries independently of harmonization process of adoption and implementation of legislation for environmental noise. Aim of this review is to summarize available evidence for noise induced sleep disturbance in population of CEE, SEE and NIS countries and to give directions for further research work in this field. After a systematic search through accessible electronic databases, conference proceedings, PhD thesis, national reports and scientific journals in English and non-English language, we decided to include six papers and one PhD thesis in this review: One paper from former Yugoslavia, one paper from Slovakia, one paper from Lithuania, two papers from Serbia and one paper, as also one PhD thesis from The Former Yugoslav Republic of Macedonia. Noise exposure assessment focused on road traffic noise was mainly performed with objective noise measurements, but also with noise mapping in case of Lithuanian study. Sleep disturbance was assessed with the questionnaire based surveys and was assumed from dose-effect relationship between night-time noise indicator (Lnight ) for road traffic noise and sleep disturbance (for Lithuanian study). Although research evidence on noise and sleep disturbance show to be sufficient for establishing dose response curves for sleep disturbance in countries where studies were performed, further research is needed with particular attention to vulnerable groups, other noise sources, development of laboratory research work and common methodology in assessment of burden of diseases from environmental noise.
Keywords: environmental noise; noise sensitivity; road traffic noise; sleep disturbance